Research on motion characteristics of space truss-crawling robot. (11th January 2019) - Tang, Tianfeng; Hou, Xuyan; Xiao, Yanni; Su, Yilin; Shi, Yuetian; Rao, Xiaoshan
For the future demands of unmanned assembly of orbital space truss structures, a new space truss-crawling robot based on biomimetic principles is proposed. The robot system mainly consists of multi-joint legs and an adhesive microstructure imitating a gecko. The kinematics analysis of a single leg and the system design are accomplished based on functional requirements and adaptivity analysis. The motion simulation model of the robot and the discrete element simulation model of the adhesion microstructure are established based upon this analysis. The simulation of the holding motion of a single leg is implemented based on the EDEM-ADAMS platform, and the feasibility of the scheme is demonstrated by analyzing the influence of adhesive microstructures comparatively. The related motion characteristics of the robot while crawling are obtained by co-simulation, and the influence law analysis is carried out by analyzing the interaction between not only the crawling infrastructure but also the crawling gait and motion characteristics. A crawling experiment in a simulated low-gravity environment is conducted to further verify the robot's movement function, which will provide beneficial reference for practical applications of the robot in the future.